STRATEGI PEMASARAN SYARIAH “BAKAR UANG” PADA PERUSAHAAN E-COMMERCE SHOPEE - Kartika Marella Vanni (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2022)
ABSTRACTIndonesian people are currently enjoying something practical and efficient. This is due to the PPKM period due to covid which occurred one year this year, so entrepreneurs racked their brains to switch to the online system and begin to integrate with their daily lives. From a variety of existing e-commerce, one of which is shopee, which is aggressively burning money and according to the data carried out by iPrice, it is recorded that this e-commerce is capable of carrying out 540 million transactions. The method used in this study uses a descriptive qualitative approach in which data collection is taken from a study of various literatures. The results of the analysis, when other companies are confused about how to maintain their company so as not to go bankrupt, shopee with its strategy is actually burning money to attract people. Shopee's promotion strategy by burning money is very effective. Which makes consumers feel more comfortable using the application, because consumers feel benefited